Insignificant events in the life of a cactus - Bowling, Dusti (Sterling Children's Books, 2017)
When thirteen-year-old Aven and her family take over a Western theme park in Arizona, she is forced into a new school. Being born with no arms, life is difficult enough, but with so many changes, Aven is desperate to connect. She then meets Connor, a boy with his own disability, and after finding a mysterious storage shed, Aven and Conner learn about the importance of friendship.